Efecto del género y del resultado final del partido en competiciones profesionales de pádel. [Effect of gender and match outcome on professional padel competition]. - Corrado Lupo (Revista Internacional de Ciencias del Deporte, 2018)
The present study aimed at analyzing the technical and tactical aspects of professional padel matches in relation to gender and match outcome. For this purpose, a notational analysis was performed on 22 official matches of the World Padel Tour 2016 by means of 18 technical and tactical indicators. A non-parametric approach was applied to evaluate differences (P ≤ 0.05) between gender and match outcome subgroups. For gender, differences emerged for the occurrence (P<0.001) and duration (P<0.001) of rallies, backhand strokes (P=0.02) and backhand volley (P=0.027), strokes close to net (P=0.001) and from midfield zone (P=0.012), smashes determining ball out (P<0.001), and first service faults (P<0.001). For match outcome, a difference was found only for the occurrence of winning rallies (in general: P<0.001; in female performance: P=0.009; in male performance: P=0.001). Although findings highlight that padel performance can be discriminated only for gender, whereas winning and losing performances resulted similar, probably for the influence of different playing styles, this study could represent a valuable reference for further analyses and more effective padel training plans.